Breast cancer‐specific survival by age: Worse outcomes for the oldest patients. Issue 10 (2nd March 2018) - Freedman, Rachel A.; Keating, Nancy L.; Lin, Nancy U.; Winer, Eric P.; Vaz‐Luis, Ines; Lii, Joyce; Exman, Pedro; Barry, William T.
Abstract : BACKGROUND: Although breast cancer often is perceived to be indolent in older women, breast cancer outcomes in the oldest patients are variable. In the current study, the authors examined breast cancer‐specific death by age, stage, and disease subtype in a large, population‐based cohort. METHODS: Using Surveillance, Epidemiology, and End Results data, a total of 486, 118 women diagnosed with American Joint Committee on Cancer stage I to IV breast cancer between 2000 and 2012 were identified. Using a series of Fine and Gray regression models to account for competing risk, the authors examined the risk of breast cancer‐specific death by age and stage (I‐IV) for subcohorts with hormone receptor (HR)‐positive, HR‐negative, human epidermal growth factor receptor 2‐positive, and triple‐negative disease, adjusting for demographic and clinical variables. RESULTS: Overall, 18% of women were aged 65 to 74 years, 13% were aged 75 to 84 years, and 4% were aged ≥85 years. Regardless of stage of disease within the HR‐positive and HR‐negative cohorts, patients aged ≥75 years (vs those aged 55‐64 years) experienced a higher adjusted hazard of breast cancer‐specific death, which was particularly evident for those with early‐stage, HR‐positive disease (hazard ratio for those aged 75‐84 years, 1.88 [95% confidence interval, 1.68‐2.09] and hazard ratio for those aged ≥85 years, 3.59 [95% confidence interval, 3.12‐4.13] [both for stage I disease]). In the cohorts with human epidermal growth factor receptor 2‐positive and triple‐negative disease, women aged ≥70 years had a consistently higher risk of breast cancer‐specific death across disease stages (vs those aged 51‐60 years), with the exception of stage IV triple‐negative disease. CONCLUSIONS: Older patients experience worse breast cancer outcomes, regardless of disease subtype and stage. With an increasing number of older patients anticipated to develop breast cancer in the future, addressing disparities for older patients must emerge as a clinical and research priority. Cancer 2018;124:2184‐91 . © 2018 American Cancer Society . Abstract : Older patients experience worse breast cancer outcomes, regardless of disease subtype and stage. Addressing disparities for older patients must emerge as a clinical and research priority.